Lignin-Glyoxal Bio-Adhesive Based on Lignin from Sugarcane Bagasse: Characterization and Application - Arrusli, Qonita; Sitorus, Berlian; Syahbanu, Intan (Trends in Sciences, 2024)
This study explores the potential of lignin extracted from sugarcane bagasse as an eco-friendly alternative to petroleum-derived phenol-formaldehyde (PF) adhesives. PF adhesives are widely used in plywood manufacturing, but their reliance on non-renewable resources and the toxicity of phenol and formaldehyde pose sustainability and health concerns. The researchers aimed to develop a lignin-glyoxal (LG) bio-adhesive that could match the performance of commercial PF adhesives. Lignin was isolated through alkali treatment, yielding 17.46 ± 3.61 %. FT-IR spectrophotometry and GPC characterization confirmed typical lignin functional groups, with Mn and Mw values of 1068.0 and 1196.0 g/mol, respectively. UV-Vis spectrophotometry revealed active sites with a total phenolic hydroxyl content of 0.35 ± 0.01 mmol/g. The optimal LG bio-adhesive composition was 1:2, achieving a tensile strength of 0.45 ± 0.06 N/mm², comparable to PF standards. While the LG 1:2 bio-adhesive exhibited suitable physicochemical properties and passed water resistance tests, it failed wet tensile strength tests, indicating its potential for interior wood product applications. This research contributes to the development of sustainable industrial applications utilizing lignin-based bio-adhesives. HIGHLIGHTS Sustainable use of sugarcane bagasse: Successfully isolated lignin from sugarcane bagasse, demonstrating a valuable use of agricultural waste for producing bio- Advanced characterization techniques: Employed FT-IR, GPC, and UV-Vis spectroscopy to comprehensively characterize lignin, providing insights into its structure and suitability for bio-adhesive applications. Effective bio-adhesive formulation: Developed a lignin-glyoxal bio-adhesive with promising adhesive properties comparable to commercial adhesives, showcasing the potential for industrial applications. Improved tensile properties: The 1:2 lignin-glyoxal bio-adhesive achieved optimal tensile properties, indicating higher cross-linking and better polymerization. Environmental benefits: Developing a bio-adhesive from renewable resources reduces dependency on fossil-fuel-based adhesives and promotes environmental sustainability. GRAPHICAL ABSTRACT